The influence of teacher work motivation and principal situational leadership on the quality of SMK Krisanti Jakarta - Nirmala, Yanti (Institute of Computer Science (IOCS), 2024)
This research obtained the results that there is an influence of teacher work motivation on improving the quality of teaching and learning, as well as the situational leadership implemented in this school also influences the quality of teachers' teaching and learning, both partial and simultaneous testing using SPSS, where the number of respondents in this study is 30 teachers at Krisanti Vocational School. The tests carried out are validity tests, reliability tests, classic assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, coefficient of determination tests, partial tests and simultaneous tests. If the principal's motivation and situational leadership are improved, the quality of teaching and learning will also increase automatically